Colección Psicología y Ley - Arce, Ramón (De Gruyter, 2020)
The 'Colección Psicología y Ley' was created by the Sociedad Española de Psicología Jurídica y Forense [Spanish Society of Forensic Psychology] with the aim of publishing the proceedings of the Society conferences. The proceedings consist of a selection of empirical unpublished papers and systematic and meta-analytic reviews of contributions presented to the conference of the Society on topics dealing with the intersection between psychology and law (e.g., testimony assessment, prison inmate treatment, community batterer treatment, forensic psychological injury assessment, child-to-parent violence, eyewitness testimony, legal decision making). The contributions have to lead knowledge transfer from scientific research to professional practice as a forensic psychologist. New applications and scientific evidence-based practices of psychology to law issues are especially welcome. The applications must be inserted in a legal framework (i.e., that to which the application was designed) and all the applications must meet with all the scientific (e.g., reliable and valid measures, forensic or statistical significance,) and specific legal requirements (e.g., testimony based in hypnosis is not permitted by Spanish laws, so applications based in this technique are not legally admissible penitentiary treatment is voluntary, so offenders may not be forced to be treated). When appropriate and possible, a strict decision criterion for practitioners should be reported. Data normally involves the assessment of subjects, therefore they must be processed in accordance with national data protection law (where they were obtained or processed) and authors are urged to review the supplement to the APA ethical list. The manuscripts are reviewed by two blind referees. The reviews are anonymous for authors and reviewers. Author identities are removed before sending out a manuscript to the reviewers.